Orofacial Clefts: Genetics of Cleft Lip and Palate - Arwa Babai; Melita Irving (2023)
Orofacial clefting is considered one of the commonest birth defects worldwide. It presents as cleft lip only, isolated cleft palate or cleft lip and palate. The condition has a diverse genetic background influenced by gene–gene and gene–environment interaction, resulting in two main types, syndromic and nonsyndromic orofacial clefts. Orofacial clefts lead to significant physiological difficulties that affect feeding, speech and language development and other developmental aspects, which results in an increased social and financial burden on the affected individuals and their families. The management of cleft lip and palate is solely based on following a multidisciplinary team approach. In this narrative review article, we briefly summarize the different genetic causes of orofacial clefts and discuss some of the common syndromes and the approach to the management of orofacial clefts.